2024
DOI: 10.1002/jmv.29724
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the burden and determinants of HIV in the Asia‐Pacific region (1990−2019): An age‐period‐cohort analysis of the 2019 Global Burden of Disease Study

Jing Li,
Dan‐Dan Xie,
Hao‐Liang Cui
et al.

Abstract: Although the burden of the human immunodeficiency virus (HIV) in the Asia‐Pacific region is increasingly severe, comprehensive evidence of the burden of HIV is scarce. We aimed to report the burden of HIV in people aged 15−79 years from 1990 to 2019 using data from the Global Burden of Disease Study (GBD) 2019. We analyzed rates of age‐standardized disability‐adjusted life years (ASDR), age‐standardized mortality (ASMR), and age‐standardized incidence (ASIR) in our age‐period‐cohort analysis by sociodemographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The analysis focused on the prevalence and number of infertility cases, as well as the estimated annual percentage change (EAPC) in age-standardized prevalence rates for both sexes over the 31-year period. Given that the Asia-Pacific region theoretically includes 39 countries, this study narrowed its focus to the 29 countries identified in recent research by The Joint United Nations Programme on HIV/AIDS (UNAIDS) ① ( 4 ). Infertility prevalence number was determined by the total number of cases within the population, while the prevalence rate was calculated per 100,000 population.…”
mentioning
confidence: 99%
“…The analysis focused on the prevalence and number of infertility cases, as well as the estimated annual percentage change (EAPC) in age-standardized prevalence rates for both sexes over the 31-year period. Given that the Asia-Pacific region theoretically includes 39 countries, this study narrowed its focus to the 29 countries identified in recent research by The Joint United Nations Programme on HIV/AIDS (UNAIDS) ① ( 4 ). Infertility prevalence number was determined by the total number of cases within the population, while the prevalence rate was calculated per 100,000 population.…”
mentioning
confidence: 99%